Methods and models for computer aided MEMS design - Teslyuk, V.; Karkulyovskyy, V.; Lobur, M.; Pereyma, M.; Denysyuk, P. (Українські технології, 2006)
In this paper an analysis of MEMS design features has been conducted. At the basis of that analysis an implementation of algorithmic aspect in MEMS design is proposed.
Keywords: microelectronics; MEMS; CAD